Window glass resistant to high temperature and high pressure and having high chemical stability, and preparation method and application thereof
By optimizing the component proportion and continuous melting process of the window glass, the high temperature and high pressure resistance and chemical stability of the window glass are improved, the problem of insufficient performance in the existing technology is solved, higher operating temperature and stability are achieved, and the Its application scope.
Patent Information
- Application Number
- CN202410104100.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-01-24
- Publication Date
- 2024-12-24
- Estimated Expiration
- 2044-01-24
AI Technical Summary
The existing window glass has insufficient performance in terms of high temperature and high pressure resistance and chemical stability, making it difficult to meet the demanding needs of petrochemicals, power and electrical, aerospace, and deep-sea exploration, especially the maximum service temperature and chemical stability are difficult to improve.
By optimizing the component ratio of the window glass, including SiO2, Al2O3, Y2O3, ZrO2, Sb2O3, TiO2, HfO2, B2O3 and RO content, 22% to 34% SiO2, 20% to 35% Al2O3, 20% and 20% were designed to obtain 22% to 34% SiO2, 20% to 35% Al2O3, 20% ~25% Y2O3, 3% to 5% ZrO2 and other components are prepared by continuous melting process to improve the glass transition temperature, relaxation temperature and mechanical properties, and physical tempering treatment to improve performance.
The maximum operating temperature of window glass is greater than 830℃, which significantly improves the ability to resist high temperature and pressure and chemical stability, meets higher usage requirements, and expands its fields in petrochemical, power and electrical, aerospace and deep-sea exploration. Application scope.
Smart Images

Figure CN118026523B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of glass technology, and in particular to a window glass that is resistant to high temperature and high pressure and has high chemical stability, and a preparation method and application thereof. Background Art
[0002] With the development of technology in specific fields such as petrochemicals, electric power, aerospace and deep-sea exploration, the application environment of window glass has become more and more demanding. Existing window glass generally has poor pressure and temperature resistance, and the above fields require window glass to meet higher application indicators. Therefore, the performance of most window glass on the market is difficult to meet the use requirements of high temperature and high pressure resistance. At the same time, the harsh environment puts forward higher requirements on the corrosion resistance of window glass. In addition to the high temperature and high pressure resistance indicators, window glass must also have the property of high chemical stability.
[0003] The Chinese invention patent with the publication number CN110372204A discloses a high temperature and high pressure resistant window glass and its preparation method and application. The window glass comprises the following components in weight percentage: SiO2: 35% to 50%; Al2O3: 10% to 15%; B2O3: 1% to 4%; R'O: 7% to 13%; ZrO2: 6% to 10%; HfO2: 2% to 6%; La2O3: 6% to 10%; Y2O3: 15% to 20%; Sb2O3: 0.5% to 1%; the sum of the weight percentages of the above components is 100%; R' is an alkaline earth metal; the components are weighed in proportion, mixed evenly and then melted, the glass liquid is clarified and homogenized by bubbling, mechanical stirring and electrode heating, and then formed and annealed. The invention solves the problem of window glass's resistance to high temperature and high pressure and difficulty in controlling its optical uniformity in the prior art, and realizes the preparation of window glass with high optical uniformity and high operating temperature and pressure. However, the maximum operating temperature of the window glass is generally 700°C, and even after tempering, the maximum operating temperature is only increased to 720°C to 782°C, which is difficult to meet higher usage requirements.
[0004] The Chinese invention patent with publication number CN102092938A provides a glass for a liquid level observation window of a liquid level gauge and a liquid level gauge. The glass for the liquid level observation window of the liquid level gauge contains 20wt.% to 30wt.% SiO2, 15wt.% to 20wt.% Al2O3, 25wt.% to 30wt.% Y2O3, 15wt.% to 20wt.% La2O3, 4wt.% to 10wt.% TiO2, and 5wt.% to 10wt.% ZrO2. The glass for the observation window has high chemical stability, will not corrode even in long-term use, and has excellent alkali resistance. However, the high content of TiO2 in its components can easily cause the glass to appear yellow and affect the transmittance of light in the glass.
[0005] Therefore, providing a window glass that meets higher performance indicators has important significance and application prospects. Summary of the invention
[0006] In view of the above-mentioned defects of the prior art, in a first aspect of the present invention, a window glass having high temperature and pressure resistance and high chemical stability is provided, which comprises the following components in terms of mass percentage:
[0007] SiO2: 22%~34%;
[0008] Al2O3: 20%~35%;
[0009] Y2O3: 20%~25%;
[0010] La2O3: 20%~25%;
[0011] ZrO2: 3% to 5%;
[0012] Sb2O3: 0.1%~0.3%;
[0013] TiO2: 0-2%;
[0014] HfO2: 0-1%;
[0015] B2O3: 0~2.5%;
[0016] RO: 0-3%;
[0017] The sum of the mass percentages of the above components is 100%; RO represents alkaline earth oxide.
[0018] Preferably, the alkaline earth oxide includes at least one of MgO, CaO, BaO and SrO.
[0019] Preferably, the content of SiO2 is 22% to 24%; the content of TiO2 is 1% to 2%; and the content of Y2O3 is 22% to 25%.
[0020] Preferably, the thermal performance indicators of the window glass are as follows: glass transition temperature (Tg) is 835-900°C; sag temperature (Ts) is 1024-1100°C; expansion coefficient is 45-59·10 -7 / K.
[0021] Preferably, the mechanical properties of the window glass are as follows: Kerr hardness (HK) is 630-700·10 7 Pa; elastic modulus is 120~160GPa; shear modulus is 46~60GPa.
[0022] Preferably, the chemical performance indicators of the window glass determined by the powder method are as follows: water resistance (D W )1 level; acid resistance (D A )Level 1.
[0023] Preferably, the upper limit temperature range of crystallization of the window glass is 1350-1420°C.
[0024] Preferably, the visible light transmittance of the window glass is ≥88%.
[0025] The window glass of the component of the present invention has good processability and does not require complicated preparation processes. It can be processed by a continuous melting production line generally applicable in the industry. Based on the upper temperature range of crystallization of the window glass of the present invention, its processing is suitable for platinum leak molding or single crucible casting molding.
[0026] In the second aspect of the present invention, a method for preparing the window glass of the first aspect of the present invention is provided, which has a simple process and wide processing applicability. The method adopts a continuous melting process, and the raw material components are mixed and then processed and formed through a continuous melting production line.
[0027] Preferably, after the processing and forming is completed, the window glass can be tempered by physical tempering.
[0028] In the third aspect of the present invention, there is provided an application of the window glass of the first aspect of the present invention or the window glass prepared by the method of the second aspect, specifically as a glass material in petrochemical, electric power, aerospace and deep-sea exploration.
[0029] Based on the above technical solutions, for performance and production considerations, the design concept and principle of the present invention are as follows:
[0030] As a glass former, SiO2 is one of the necessary components of glass. Under optimized conditions, its design content is controlled at 22% to 24%. This is because when it is lower than 22%, the glass crystallization performance is enhanced, which is not conducive to glass formation. Since the elastic modulus of SiO2 is 6.2 to 7.3·10 -7 kg / cm 2 When it is higher than 24%, it is not conducive to improving the bending resistance of the window glass.
[0031] Al2O3 is used as a glass network former, and its design content is controlled to be 20% to 35%. The elastic modulus of Al2O3 is 11kg / cm 2 When the content is lower than 20%, it is not conducive to improving the mechanical properties of the glass (such as hardness, elastic modulus and shear modulus, etc.), and it also does not utilize the crystallization performance and molding temperature control; Al2O3 has a high melting point, and when its content is higher than 35%, it will cause difficulties in melting the glass and is not conducive to processing.
[0032] Y2O3 is one of the essential components for improving the chemical stability and high temperature resistance of glass. The designed content of the present invention is 20-25%. When it is lower than 20%, the chemical stability and high temperature resistance of glass will be reduced; and when it is higher than 25%, the crystallization performance of glass will be reduced.
[0033] La2O3 is a component that has the same effect of improving the chemical stability and high temperature resistance of glass as Y2O3. When the two are used together, they have a mixed rare earth element effect similar to the mixed alkali effect, which is beneficial to improving the mechanical strength and high temperature resistance of glass. Therefore, the content of La2O3 designed by the present invention is 20% to 25%. When the content is lower than 20%, the chemical stability of glass will be reduced; and when it is higher than 25%, the crystallization performance of glass will also be reduced.
[0034] ZrO2 is used as a necessary component to reduce the expansion coefficient and improve the chemical stability in the present invention, and its content is designed to be 3-5%. This is because when the content is lower than 3%, the chemical stability cannot be achieved; when it is higher than 5%, it is difficult to melt and the crystallization performance of the glass will deteriorate during production.
[0035] TiO2 is one of the components of the present invention that reduces the glass expansion coefficient and improves the mechanical strength and high temperature resistance of glass. Its designed content is not higher than 2%, and the preferred content is 1% to 2%. The elastic modulus of TiO2 is 13 to 19 kg / cm 2 If the content is lower than 1%, it will be difficult to improve the mechanical strength; if the content is higher than 2%, the glass will appear yellow and affect the visible light transmittance of the glass.
[0036] The elastic modulus of HfO2 is 20kg / cm 2 When the content is not higher than 1%, it helps to improve the mechanical strength of the glass. When it is higher than 1%, due to the melting point of HfO2 is 2758℃ and the high density (9.68g / cm 3 ), it is not easy to mix and melt evenly, which will reduce the processability of production.
[0037] B2O3, as one of the glass formers, helps to melt and increase the low-band transmittance of glass. The designed content of the present invention is not higher than 2.5%. Since there is no alkali in the formula system, if the content exceeds this amount, it will cause the boron oxygen polyhedron to change, causing the crystallization performance to change.
[0038] RO (alkaline earth oxide) is used as a regulating oxide for the glass expansion coefficient, viscosity and mechanical properties in this formula system, and its designed content is not higher than 3%. A content higher than this will lead to a decrease in the chemical stability of the glass.
[0039] Sb2O3 is used as a clarifier in the present invention, and a content of 0.1%-0.3% can meet the demand for bubble clarification.
[0040] Compared with the prior art, the present invention has the following advantages and beneficial effects:
[0041] The present invention provides a window glass which adopts a specific component design, and the maximum use temperature of the window glass before crystallization is greater than 830° C., thereby improving the high temperature and high pressure resistance and chemical stability of the window glass.
[0042] The present invention provides a method for preparing window glass, which can take into account the needs of continuous production by continuous melting in a kiln based on the component design of the window glass.
[0043] The present invention also provides an application of window glass, and the window glass with high performance indicators expands its application scope in petrochemical industry, electric power, aerospace and deep-sea exploration. BRIEF DESCRIPTION OF THE DRAWINGS
[0044] Figure 1 is an expansion curve diagram of the window glass of Example 1;
[0045] Figure 2 is an expansion curve diagram of the window glass of Example 2;
[0046] Figure 3 is an expansion curve diagram of the window glass of Example 3;
[0047] Figure 4 is an expansion curve diagram of the window glass of Example 4;
[0048] Figure 5 is an expansion curve diagram of the window glass of Example 5;
[0049] Figure 6 is an expansion curve diagram of the window glass of Example 6; DETAILED DESCRIPTION
[0050] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions, or selected according to the product specifications.
[0051] Example 1
[0052] In this embodiment, the raw materials are mixed evenly, and after melting and forming in a single crucible and continuous melting production line, a window glass can be obtained; the window glass of this embodiment is composed of the following components in the following proportions:
[0053] SiO2: 23.10%;
[0054] Y2O3: 20.79%;
[0055] Sb2O3: 0.107%;
[0056] La2O3: 22.58%;
[0057] ZrO2: 4.0%;
[0058] TiO2: 1.93%;
[0059] Al2O3: 25.11%;
[0060] B2O3: 1.22%;
[0061] HfO2: 0.1%;
[0062] MgO: 1.0%.
[0063] In actual preparation, due to the purity of raw materials and the inherent error of equipment, the actual total mass percentage will fluctuate within an acceptable range above and below the theoretical value (100%). The mass percentage of the above components totals 99.937%, with extremely low deviation, and can be regarded as being proportioned according to the theoretical value.
[0064] Example 2
[0065] In this embodiment, the raw materials are mixed evenly, and after melting and forming in a single crucible and continuous melting production line, a window glass can be obtained; the window glass of this embodiment does not contain MgO (i.e., the content is 0%), and is composed of the following components in the following proportions:
[0066] SiO2: 22.41%;
[0067] Y2O3: 24.21%;
[0068] Sb2O3: 0.107%;
[0069] La2O3: 23.52%;
[0070] ZrO2: 4.0%;
[0071] TiO2: 1.00%;
[0072] Al2O3: 22.12%;
[0073] B2O3: 2.44%;
[0074] HfO2: 0.1%.
[0075] The mass percentage of the above components totals 99.907%, which can be regarded as being proportioned according to theoretical values.
[0076] Example 3
[0077] In this embodiment, the raw materials are mixed evenly, and after melting and forming in a single crucible and continuous melting production line, a window glass can be obtained; the window glass of this embodiment does not contain B2O3, and is composed of the following components in the following proportions:
[0078] SiO2: 24.69%;
[0079] Y2O3: 22.74%;
[0080] Sb2O3: 0.109%;
[0081] La2O3: 22.73%;
[0082] ZrO2: 4.5%;
[0083] TiO2: 1.50%;
[0084] Al2O3: 23.22%;
[0085] HfO2: 0.1%;
[0086] MgO: 0.5%.
[0087] The mass percentages of the above components total 100.089%, which can be regarded as being proportioned according to theoretical values.
[0088] Example 4
[0089] In this embodiment, the raw materials are mixed evenly, and after melting and forming in a single crucible and continuous melting production line, a window glass can be obtained; the window glass of this embodiment does not contain B2O3 and MgO, and is composed of the following components in the following proportions:
[0090] SiO2: 25.15%;
[0091] Y2O3: 24.21%;
[0092] Sb2O3: 0.103%;
[0093] La2O3: 22.81%;
[0094] ZrO2: 4.5%;
[0095] TiO2: 1.00%;
[0096] Al2O3: 22.15%;
[0097] HfO2: 0.1%.
[0098] The mass percentages of the above components total 100.023%, which can be regarded as being proportioned according to theoretical values.
[0099] Example 5
[0100] In this embodiment, the raw materials are mixed evenly, and after melting and forming in a single crucible and continuous melting production line, a window glass can be obtained; the window glass of this embodiment does not contain B2O3 and MgO, and is composed of the following components in the following proportions:
[0101] SiO2: 20.38%;
[0102] Y2O3: 21.00%;
[0103] Sb2O3: 0.112%;
[0104] La2O3: 25.00%;
[0105] ZrO2: 4.5%;
[0106] TiO2: 2.00%;
[0107] Al2O3: 26.80%;
[0108] HfO2: 0.2%.
[0109] The mass percentages of the above components total 99.992%, which can be regarded as being proportioned according to theoretical values.
[0110] Example 6
[0111] In this embodiment, the raw materials are mixed evenly, and after melting and forming in a single crucible and continuous melting production line, a window glass can be obtained; the window glass of this embodiment does not contain TiO2, B2O3, and MgO, and is composed of the following components in the following proportions:
[0112] SiO2: 30.00%;
[0113] Y2O3: 24.48%;
[0114] Sb2O3: 0.109%;
[0115] La2O3: 20.00%;
[0116] ZrO2: 5.0%;
[0117] Al2O3: 20.00%;
[0118] HfO2: 0.5%.
[0119] The mass percentages of the above components total 100.089%, which can be regarded as being proportioned according to theoretical values.
[0120] The comprehensive performance of the window glass of the above embodiment was tested, wherein:
[0121] The elastic modulus and shear modulus are measured according to the method and procedures specified in GB / T 7962.6-2010 "Test methods for colorless optical glass Part 6: Young's modulus, shear modulus and Poisson's ratio";
[0122] The transition temperature, sag temperature and expansion coefficient are measured according to the method and steps specified in GB / T 7962.16-2010 "Test methods for colorless optical glass Part 16: Linear expansion coefficient, transition temperature and sag temperature";
[0123] Kirschner hardness is measured according to the method and steps specified in GB / T 7962.18-2010 "Test methods for colorless optical glass Part 18: Kirschner hardness";
[0124] Chemical properties include water resistance stability and acid resistance stability, which are measured according to the method and steps specified in JB / T 10576-2006 "Chemical Stability Test Method for Colorless Optical Glass - Powder Method";
[0125] The crystallization temperature is tested according to the method specified in the international standard ASTM E228-22;
[0126] The visible light transmittance was measured by a standard measuring instrument, and the thickness of the glass sample used in the test was 10 mm;
[0127] The test results of the above tests are shown in Table 1.
[0128] Table 1:
[0129]
[0130] The above test results show that the design of the component content of the window glass of the present invention is helpful to improve the performance, and the use temperature of the window glass is greater than 830°C. Figures 1 to 6 The expansion curves of the window glasses of Examples 1 to 6 are shown in turn, and the window glasses of the present invention have excellent resistance to high temperature and high pressure, chemical stability and visible light transmittance, and can meet the application requirements in the fields of petrochemical, electric power, aerospace and deep sea exploration.
[0131] The preferred specific embodiments of the present invention are described in detail above. It should be understood that a person skilled in the art can make many modifications and changes based on the concept of the present invention without creative work. Therefore, any technical solution that can be obtained by a person skilled in the art through logical analysis, reasoning or limited experiments based on the concept of the present invention on the basis of the prior art should be within the scope of protection determined by the claims.
Claims
1. A window glass, characterized in that: In terms of mass percentage, it is composed of the following components: SiO2: 22%~24%; Al2O3: 20%~35%; Y2O3: 20%~ <25%; La2O3: 22.58%~25%; ZrO2: 3%~5%; Sb2O3: 0.1%~0.3%; TiO2: 1%~2%; HfO2: 0.1%~1%; B2O3: 1.22%~2.5%; RO: 0.5%~3%; The sum of the mass percentages of the above components is 100%; RO represents alkaline earth oxide, including at least one of MgO, CaO, BaO, and SrO; The thermal performance indicators of window glass are as follows: glass transition temperature is 835~900℃; sag temperature is 1024~1100℃; expansion coefficient is 45~59·10 -7 / K; The Kirkmar hardness of window glass is 630~700·10 7 Pa; elastic modulus is 120~160GPa; shear modulus is 46~60GPa; The chemical performance indicators of window glass determined by the powder method are as follows: water resistance level 1; acid resistance level 1; The upper temperature range of crystallization of window glass is 1350~1420℃; The visible light transmittance of the window glass is ≥88%.
2. A method for preparing window glass as claimed in claim 1, using a continuous melting process, characterized in that: The material is prepared by mixing various raw material components and then processing and molding them through a continuous melting production line.
3. Use of the window glass according to claim 1 or the window glass prepared by the method according to claim 2, characterized in that: Applications of glass materials in petrochemical industry, electric power, aerospace and deep sea exploration.
